Powder containing α,α-trehalose dihydrate crystals, and its production method and use

By preparing a trehalose dihydrate crystal powder with specific sugar ratios and aging conditions, the emulsification ability of trehalose dihydrate crystals is significantly enhanced, addressing the limitations of conventional powders and enabling effective dispersion of oily substances in water across diverse fields.

CN115287377BActive Publication Date: 2024-12-24NAGASE VIITA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210870637.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2016-01-20
Filing Date
2017-01-19
Publication Date
2024-12-24
Estimated Expiration
2037-01-19

AI Technical Summary

Technical Problem

Conventional trehalose dihydrate crystal-containing powders lack effective emulsification ability to disperse oily substances in water.

Method used

A method involving the preparation of a sugar solution with specific trehalose, maltose, and/or maltotriose ratios, followed by spray-drying and ripening under high humidity to convert amorphous trehalose into trehalose dihydrate crystals, resulting in a powder with enhanced emulsifying properties.

Benefits of technology

The resulting powder exhibits superior emulsifying ability, allowing for effective dispersion of hydrophobic substances in water, suitable for various applications including food, cosmetics, and pharmaceuticals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115287377B_ABST
    Figure CN115287377B_ABST
Patent Text Reader

Abstract

The present invention relates to a powder containing α,α-trehalose dihydrate crystals, a method for producing the same and uses thereof. The subject of the present invention is to provide a powder containing α,α-trehalose dihydrate crystals having excellent emulsification ability. The means for solving the above-mentioned problems is to provide a powder containing α,α-trehalose dihydrate crystals, which comprises particles containing α,α-trehalose, maltose and / or maltotriose, characterized in that it contains 70% to 90% by mass of α,α-trehalose converted to anhydrous form, and contains a total of more than 3% by mass of maltose and / or maltotriose converted to anhydrous form, and the crystallinity of the α,α-trehalose dihydrate crystals calculated based on the powder X-ray diffraction pattern is more than 25% and less than 90%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese patent application No. 201780015286.2 with the same invention name. The original international application number is PCT / JP2017 / 001718, and the international application date is January 19, 2017. Technical Field

[0002] The present invention relates to a powder containing α,α-trehalose dihydrate crystals, a method for producing the same, and uses thereof, and more particularly to a powder containing α,α-trehalose dihydrate crystals having excellent emulsification ability, a method for producing the same, and uses thereof. Background Art

[0003] α,α-Trehalose (hereinafter referred to as "trehalose" in this specification) is a non-reducing disaccharide in which two glucose molecules are bonded in an α,α-1,1 manner. It has excellent effects such as inhibiting starch aging, inhibiting water separation of food, inhibiting denaturation / coagulation of protein, stabilizing bubbles in meringues, inhibiting deterioration of lipids, inhibiting the generation of heated odor of fruits or milk, etc., protecting tissues during freezing, inhibiting browning of fruits / vegetables, and correcting flavor / odor. Therefore, it is widely used in foods, cosmetics, and quasi-drugs. In addition, it is also widely used in pharmaceuticals as an excipient for tablets or a stabilizer for physiologically active substances.

[0004] As a method for producing trehalose, various methods are known. For example, Patent Document 1 discloses a method for producing a powder containing trehalose dihydrate crystals, wherein α-glycosyltrehalose synthase and trehalose separating enzyme are acted on liquefied starch together with starch debranching enzyme and cyclodextrin-glucan transferase, and then acted with grape amylase to prepare a sugar solution containing trehalose, and then trehalose is crystallized from the obtained sugar solution containing trehalose. The applicant manufactures a powder containing high-purity trehalose dihydrate crystals (trade name "Treha", sold by Hayashihara Co., Ltd., with a purity of 98% by mass or more. Hereinafter referred to as "the conventional powder containing trehalose dihydrate crystals") by the manufacturing method disclosed in Patent Document 1, which is mainly sold as food materials, cosmetic materials, etc. The conventional powder containing trehalose dihydrate crystals has extremely excellent storage stability, and even if stored under high humidity, it hardly changes due to moisture absorption, and the usability is very good. However, conventional powders containing trehalose dihydrate crystals have hardly shown an effect of dispersing oily substances such as fats and oils in water (ie, so-called emulsifying ability).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Patent No. 3793590 Summary of the invention

[0008] Problems to be solved by the invention

[0009] An object of the present invention is to solve the above-mentioned disadvantages of the conventional trehalose dihydrate crystal-containing powder and to provide a trehalose dihydrate crystal-containing powder having excellent emulsification ability, and a method for producing the same and use thereof.

[0010] Means of solving problems

[0011] In order to solve the above-mentioned problems, the present inventors paid attention to the emulsifying ability of a powder containing trehalose dihydrate crystals. During intensive studies, they unexpectedly found that a powder containing trehalose dihydrate crystals having excellent emulsifying ability can be obtained by preparing a sugar solution containing trehalose, maltose and / or maltotriose in a predetermined ratio, spray-drying the sugar solution to powderize the sugar solution, and ripening the obtained powder under high humidity to convert part of the amorphous trehalose into trehalose dihydrate crystals. The present invention has been completed.

[0012] That is, the present invention solves the above-mentioned problems by providing a powder containing trehalose dihydrate crystals having the following characteristics (1) to (3), wherein the powder containing trehalose dihydrate crystals comprises particles containing trehalose, maltose and / or maltotriose.

[0013] (1) containing 70% by mass or more and 90% by mass or less of trehalose calculated as anhydrous;

[0014] (2) containing 3% by mass or more of maltose and / or maltotriose in total, calculated as anhydrous; and

[0015] (3) The crystallinity of the trehalose dihydrate crystals calculated based on the powder X-ray diffraction pattern is 25% or more and less than 90%.

[0016] From the perspective of a production process of spray-drying a sugar solution containing trehalose, maltose and / or maltotriose at a predetermined ratio, the powder containing trehalose dihydrate crystals of the present invention is a powder containing trehalose dihydrate crystals that at least includes particles containing trehalose, maltose and / or maltotriose.

[0017] The present invention also solves the above-mentioned problems by providing a method for producing a powder containing trehalose dihydrate crystals having the above-mentioned characteristics (1) to (3), wherein the method comprises the following steps: a step of preparing a sugar solution containing 70% by mass or more and 90% by mass or less of trehalose calculated as an anhydrous substance and containing 3% by mass or more of maltose and / or maltotriose in total calculated as an anhydrous substance; a step of powdering the sugar solution by spray drying; a step of crystallizing trehalose dihydrate crystals by aging the obtained powder at a relative humidity of 60% or more for 7 days or more; and a step of drying the obtained powder containing trehalose dihydrate crystals.

[0018] Furthermore, the present invention solves the above-mentioned problems by providing an emulsifier containing a powder containing trehalose dihydrate crystals having the above-mentioned characteristics (1) to (3), wherein the powder containing trehalose dihydrate crystals comprises particles containing trehalose, maltose and / or maltotriose.

[0019] Effects of the Invention

[0020] The powder containing trehalose dihydrate crystals of the present invention has a superior emulsifying ability compared to conventional powder containing trehalose dihydrate crystals, and can be widely used in various fields including the food field and the cosmetic field. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] [ Figure 1 ] A scanning electron microscope photograph (magnification 300 times) of the powder 1 containing trehalose dihydrate crystals obtained in Experiment 1-1 (aged for 7 days at a relative humidity of 75%).

[0022] [ Figure 2 ] A scanning electron microscope photograph (magnification 300 times) of the powder 3 containing trehalose dihydrate crystals obtained in Experiment 1-1 (aged for 7 days at a relative humidity of 75%).

[0023] [ Figure 3 ] A scanning electron microscope photograph (magnification 300 times) of the powder 4 containing trehalose dihydrate crystals obtained in Experiment 1-1 (aged for 7 days at a relative humidity of 75%).

[0024] [ Figure 4 ] A scanning electron microscope photograph (magnification 300 times) of the powder 5 containing trehalose dihydrate crystals obtained in Experiment 1-1 (aged for 7 days at a relative humidity of 75%).

[0025] [ Figure 5 ] A scanning electron microscope photograph (magnification 300 times) of the powder 9 containing trehalose dihydrate crystals obtained in Experiment 1-1 (aged for 7 days at a relative humidity of 75%). DETAILED DESCRIPTION

[0026] 1. Definition of terms

[0027] In this specification, the following terms have the following meanings.

[0028] <(Sugar) Content>

[0029] The "(sugar) content" mentioned in this specification refers to the proportion (mass %) of each sugar in the total sugar measured by the following sugar composition analysis method. That is, the sugar sample is dissolved in ultrapure water to a solid content concentration of 1 mass%, filtered with a 0.45μm filter membrane, and then subjected to sugar composition analysis under the following conditions, and the ratio of the peak area of ​​each sugar on the HPLC spectrum to the total peak area is taken as the content of each sugar. HPLC analysis uses two "MCI gel CK04SS" (Mitsubishi Chemical Corporation) as a chromatographic column connected, ultrapure water is used as an eluent, and the column temperature is 80°C, the flow rate is 0.4mL / min, and the detection is carried out using a differential refractometer "RID-10A" (Shimadzu Corporation). The ratio of the peak area of ​​trehalose, maltose and maltotriose in the HPLC spectrum to the total peak area is respectively referred to as "trehalose content", "maltose content" and "maltotriose content".

[0030] <Crystallinity>

[0031] The "crystallinity of trehalose dihydrate crystals" referred to in this specification refers to a value defined by the following formula [1].

[0032] Formula [1]:

[0033]

Number 1

[0034]

[0035] H 100 : Analytical value of crystallinity obtained from powder X-ray diffraction pattern of a standard sample of powder containing trehalose dihydrate crystals which is substantially composed of trehalose dihydrate crystals

[0036] H0: Analytical value of crystallinity obtained from powder X-ray diffraction pattern of a standard sample of trehalose-containing powder consisting essentially of an amorphous portion

[0037] H s : Analytical value of crystallinity obtained from the powder X-ray diffraction pattern of the powder containing trehalose as the test sample

[0038] In formula [1], the analytical value H 100The powder X-ray diffraction pattern based on H0, Hs can usually be measured by a powder X-ray diffraction device equipped with a reflection or transmission optical system. The powder X-ray diffraction pattern includes the diffraction angle and diffraction intensity of the trehalose dihydrate crystals contained in the test sample or the standard sample. As a method for determining the analytical value of crystallinity from the powder X-ray diffraction pattern, the Harmans method is used.

[0039] In addition, the analytical value H is obtained 100 The "standard sample of powder containing trehalose dihydrate crystals which is basically composed of trehalose dihydrate crystals" uses a powder which is basically composed of trehalose dihydrate crystals, which is a powder or single crystal having a trehalose content of 99.9% by mass or more in terms of anhydrous form, and which shows a diffraction peak peculiar to trehalose dihydrate crystals in the powder X-ray diffraction pattern. Such a powder or single crystal may be a powder containing trehalose dihydrate crystals which is currently being sold by the applicant as an analytical reagent (trade name "Trehalose 999", code number: TH224, trehalose content of 99.9% or more, sold by Hayashibara Co., Ltd.), or a powder containing trehalose dihydrate crystals or a single crystal of trehalose dihydrate crystals obtained by recrystallizing the same. In addition, when the powder X-ray diffraction pattern of the standard sample containing powder containing trehalose dihydrate crystals which is basically composed of trehalose dihydrate crystals is analyzed by computer software using the Harmans method, the analytical value H 100 Usually around 50.6 to 50.9%.

[0040] On the other hand, as the "standard sample of trehalose-containing powder consisting essentially of amorphous matter" for obtaining the analysis value H0, a powder consisting essentially of amorphous matter having a trehalose content of 99.9% by mass or more in terms of anhydrous matter is used. Such a powder can be, for example, obtained by 100 The standard sample is dissolved in an appropriate amount of purified water, concentrated, freeze-dried, and then vacuum-dried until the moisture content determined by the Karl Fischer method is less than 2.0% to obtain a powder. When this treatment is carried out, a powder consisting essentially of amorphous substances is obtained, which is known from experience. However, usually, even if the powder is basically composed of amorphous substances, when the powder X-ray diffraction pattern obtained is applied to a powder X-ray diffraction device and analyzed by the Harmans method, Fonk method, etc., the analysis value is not necessarily 0% because a part of the scattered light from the amorphous substances is calculated by the algorithm of the computer software executing various analysis methods. In addition, when the powder X-ray diffraction pattern of the standard sample of the above-mentioned trehalose-containing powder consisting essentially of amorphous substances is analyzed by computer software using the Harmans method, the analysis value H0 is usually about 8.5 to 8.7%.

[0041] The Harmans method is described in detail in PH Harmans and A. Weidinger, Journal of Applied Physics, Vol. 19, pp. 491-506 (1948), and PH Harmans and A. Weidinger, Journal of Polymer Science, Vol. 4, pp. 135-144 (1949).

[0042] <Specific surface area>

[0043] The "specific surface area" as used in this specification refers to the surface area per unit mass of the powder. That is, the powder (about 2 g) was dried under reduced pressure at 40°C for 15 hours using a pretreatment device for adsorption measurement ("BELPREP-vacII", manufactured by Microtrac Bell), and then measured using an automatic specific surface area / pore distribution measurement device ("BELSORP-miniII", manufactured by Microtrac Bell) by a conventional nitrogen adsorption method, and the obtained measured value was analyzed by a conventional BET method to obtain a surface area per 1 g as the specific surface area.

[0044] <Particle Size Distribution>

[0045] The "particle size distribution" mentioned in this specification refers to the proportion (mass %) of powder of each particle size level determined by the following method. That is, according to Japanese Industrial Standard (JIS Z 8801-1), after accurately weighing sieves with mesh sizes of 425, 300, 212, 150, 106, 75 and 53 μm, they are stacked in this order and installed on a rotary sieve vibrator, and then a certain amount of the weighed sample is placed on the top sieve (mesh size 425 μm), and after oscillating for 15 minutes while the sieves are overlapped, each sieve is accurately weighed again, and the mass before the sample is placed is subtracted from the mass, thereby determining the mass of powder captured by each sieve. Then, the ratio (mass %) of the mass of powder with each particle size captured by each sieve relative to the mass of the sample placed on the sieve is obtained as the particle size distribution. In addition, as a screen, for example, a metal screen manufactured by Iida Manufacturing Co., Ltd. is used, and as a rotary sieve vibrator, for example, a rotary sieve vibrator "R-1" manufactured by Tanaka Chemical Machinery Manufacturing Co., Ltd. is used.

[0046] <Emulsifying ability>

[0047] The "emulsifying ability" mentioned in this specification refers to the ability of oil to disperse in water. Mix 5 parts by mass of powder and 1 part by mass of corn oil, then add 500 parts by mass of pure water, and measure the turbidity (absorbance at a wavelength of 720nm) of the emulsion obtained by stirring, as the value of the emulsifying ability. The higher the turbidity (absorbance at a wavelength of 720nm) of the emulsion, the higher the emulsifying ability. Specifically, the emulsifying ability can be measured as follows: for example, mix 0.25g of powder and 0.05g of corn oil (reagent, sold by Wako Pure Chemical Industries, Ltd.), then add 25g of pure water, and measure the turbidity (absorbance at a wavelength of 720nm) of the emulsion obtained by stirring using a spectrophotometer ("UV-1800", manufactured by Shimadzu Corporation).

[0048] <Maturation>

[0049] The term "aging" as used herein means maintaining amorphous sugar or powder containing the amorphous sugar under predetermined temperature and humidity conditions for a predetermined time to convert the amorphous sugar into crystalline sugar and crystallize the sugar.

[0050] 2. Powder containing trehalose dihydrate crystals

[0051] The present inventors have discovered a powder containing trehalose dihydrate crystals having excellent emulsification ability and storage stability. The powder contains particles containing trehalose, maltose and / or maltotriose, and has the following characteristics (1) to (3):

[0052] (1) containing 70% by mass or more and 90% by mass or less of trehalose calculated as anhydrous;

[0053] (2) containing 3% by mass or more of maltose and / or maltotriose in total, calculated as anhydrous; and

[0054] (3) The crystallinity of the trehalose dihydrate crystals calculated based on the powder X-ray diffraction pattern is 25% or more and less than 90%.

[0055] The first characteristic of the powder containing trehalose dihydrate crystals of the present invention is that it contains particles containing trehalose, maltose and / or maltotriose. This characteristic means that the powder containing trehalose dihydrate crystals of the present invention is produced by a whole sugar method, which means that the trehalose powder is different from the powder product obtained by simply mixing maltose powder and / or maltotriose powder.

[0056] It should be noted that the powder of the present invention contains particles containing trehalose, maltose and / or maltotriose, which can be confirmed by analyzing the sugar composition of one powder particle constituting the powder. Specifically, for example, one powder particle can be selected from the powder, dissolved in a small amount of water as a test solution, and the sugar contained in the test solution can be directly analyzed by HPLC, or labeled with a fluorescent reagent and then analyzed by HPLC. In this case, the sugar composition shown by the powder particle is basically the same as the sugar composition of the raw sugar solution. Even if there is a slight deviation in the numerical value due to the difference in the collected particles, the deviation value remains in the range of 1 to 2%. In addition, the sugar composition of one powder particle can also be confirmed by providing it for high-sensitivity analysis using a capillary electrophoresis device.

[0057] In addition, the second characteristic of the trehalose dihydrate crystal-containing powder of the present invention is that (1) it contains 70% to 90% by mass of trehalose in terms of anhydrous form. The trehalose content is derived from the trehalose content in the spray-dried raw sugar solution. The above characteristic (1) means that the trehalose dihydrate crystal-containing powder of the present invention is a powder obtained by spray-drying a sugar solution containing 70 to 90% by mass of trehalose in terms of anhydrous form. In other words, in order to obtain the trehalose dihydrate crystal-containing powder of the present invention, the trehalose content in the spray-dried sugar solution must be in the range of 70 to 90% by mass in terms of anhydrous form.

[0058] The third characteristic of the trehalose dihydrate crystal-containing powder of the present invention is (2) that it contains 3% by mass or more of maltose and / or maltotriose in total, calculated as anhydrous. The content of maltose and / or maltotriose is derived from the content of maltose and / or maltotriose in the spray-dried raw sugar solution. The characteristic (2) means that the trehalose dihydrate crystal-containing powder of the present invention is a powder obtained by spray-drying a sugar solution containing 3% by mass or more of maltose and / or maltotriose in total, calculated as anhydrous. In other words, in order to obtain the trehalose dihydrate crystal-containing powder of the present invention, the content of maltose and / or maltotriose in the spray-dried sugar solution must be 3% by mass or more in total, calculated as anhydrous.

[0059] In addition, the fourth characteristic of the powder containing trehalose dihydrate crystals of the present invention is (3) the crystallinity of the trehalose dihydrate crystals calculated based on the powder X-ray diffraction pattern is 25% or more and less than 90%. The above characteristic (3) means that the powder containing trehalose dihydrate crystals of the present invention is a powder obtained by converting a part of amorphous trehalose into trehalose dihydrate crystals by aging. In other words, in order to obtain the powder containing trehalose dihydrate crystals of the present invention, it is necessary to ripen the powder obtained by spray-drying a sugar solution containing trehalose, maltose and / or maltotriose in a specified ratio under specified conditions so that the crystallinity of the trehalose dihydrate crystals is 25% or more and less than 90%.

[0060] The reason why the powder containing trehalose dihydrate crystals and having the characteristics of (1) to (3) above, which includes particles containing trehalose, maltose and / or maltotriose, has extremely superior emulsifying ability compared to conventional powders is not determined, but it is presumed to be due to the following relationship: in each powder particle constituting the powder, trehalose in the form of dihydrate crystals and amorphous trehalose exist at a predetermined ratio, and maltose and / or maltotriose exist in a mixed state. In addition, the fact that maltose and / or maltotriose, which are sugars other than trehalose, are usually present in an amorphous state in one powder particle is also considered to be related to the emulsifying ability of the powder as a whole.

[0061] It should be noted that according to the results confirmed by the inventors, the contents of each sugar and the crystallinity of trehalose dihydrate crystals have more preferred ranges, and a powder containing trehalose dihydrate crystals containing 78 mass % or more and 86 mass % or less of trehalose on an anhydrous basis, 4 mass % or more of maltose and / or maltotriose on an anhydrous basis, and a crystallinity of trehalose dihydrate crystals of 50% or more and less than 90% has a higher emulsifying ability and is more suitable for use. In other words, a more preferred powder containing trehalose dihydrate crystals of the present invention is a powder having the following characteristics (1') to (3').

[0062] (1') containing 78 mass % or more and 86 mass % or less of trehalose calculated as anhydrous;

[0063] (2') containing 4% by mass or more of maltose and / or maltotriose in total, calculated as anhydrous; and

[0064] (3′) The crystallinity of the trehalose dihydrate crystals calculated based on the powder X-ray diffraction pattern is 50% or more and less than 90%.

[0065] The powder containing trehalose dihydrate crystals of the present invention is a powder containing particles containing trehalose, maltose and / or maltotriose, having the characteristics of (1) to (3) above, having excellent emulsification ability, but a large number of fine irregularities are observed on the surface of the particles constituting the powder, and the powder as a whole has the fifth characteristic: (4) the specific surface area of ​​the powder measured by the nitrogen adsorption method is 0.25 m 2 In particular, the specific surface area of ​​the powder containing trehalose dihydrate crystals showing an emulsification ability value of 0.45 or more is usually 0.35 m 2 As shown in Experiment 3 described later, the specific surface area of ​​the conventional powder containing trehalose dihydrate crystals is 0.18 m 2 / g, therefore, the powder containing trehalose dihydrate crystals of the present invention can be a powder showing a higher specific surface area than conventional powders containing trehalose dihydrate crystals or amorphous trehalose.

[0066] In addition, the powder containing trehalose dihydrate crystals of the present invention is not limited to having a specific particle size distribution, but generally, as a particle size distribution, it is preferred that (5) the powder contains: particles with a particle size of 53 μm or more and less than 300 μm accounting for 50% by mass of the entire powder, and particles with a particle size of less than 53 μm accounting for 10% by mass of the entire powder. When the powder containing trehalose dihydrate crystals of the present invention has the particle size distribution specified in (5) above, it can be more preferably used as a powder with higher dispersibility in liquids or powders and emulsification ability.

[0067] The trehalose dihydrate crystal-containing powder of the present invention is characterized by excellent emulsification ability. It is not limited to showing a specific emulsification ability value as long as it has a higher emulsification ability than the conventional trehalose dihydrate crystal-containing powder. Generally, (6) 500 parts by mass of pure water is added to a mixture of 5 parts by mass of the powder and 1 part by mass of corn oil, and the turbidity of the obtained emulsion at a wavelength of 720 nm after stirring is 0.35 or more, more preferably 0.45 or more. As described later, the turbidity of the emulsion when measured by the same method as the conventional trehalose dihydrate crystal-containing powder is a low value of about 0.10, so the turbidity showing a value of 0.35 or more indicates that the trehalose dihydrate crystal-containing powder of the present invention has extremely excellent emulsification ability compared with the conventional dihydrate crystal-containing powder. To the best of the knowledge of the present inventors, a trehalose dihydrate crystal-containing powder having such a high emulsification ability did not exist before the filing date of the present application.

[0068] 3. Method for producing a powder containing trehalose dihydrate crystals of the present invention

[0069] The powder containing trehalose dihydrate crystals of the present invention may be produced by any production method as long as it has the above characteristics (1) to (3), and is preferably produced by a production method including the following steps (A) to (D).

[0070] (A) a step of preparing a sugar solution containing 70% by mass or more and 90% by mass or less of trehalose calculated as anhydrous form and containing 3% by mass or more of maltose and / or maltotriose in total calculated as anhydrous form;

[0071] (B) a step of powdering the sugar solution by spray drying;

[0072] (C) a step of crystallizing trehalose dihydrate crystals by aging the obtained powder at a relative humidity of 60% or more for 7 days or more; and

[0073] (D) A step of drying the obtained powder containing trehalose dihydrate crystals.

[0074] Hereinafter, the above steps (A) to (D) will be described in order.

[0075] <Step (A) (Step of Preparing a Sugar Solution Containing Trehalose)>

[0076] This step is a step of preparing a sugar solution containing 70% to 90% by mass of trehalose in terms of anhydrous conversion, and containing 3% or more by mass of maltose and / or maltotriose in total in terms of anhydrous conversion. The method for preparing the sugar solution is not particularly limited as long as it contains 70% to 90% by mass of trehalose in terms of anhydrous conversion, and contains 3% or more by mass of maltose and / or maltotriose in total in terms of anhydrous conversion. For example, the sugar solution can be prepared by a method of allowing liquefied starch to react with glycosyltrehalose synthase and trehalose separating enzyme as disclosed in Japanese Patent No. 3557235, a method of allowing maltose-trehalose converting enzyme to react with maltose solution as disclosed in Japanese Patent No. 3633648, a method of allowing maltose phosphorylase and trehalose phosphorylase to react with maltose solution as disclosed in Japanese Patent Publication No. 63-060998, and the like. Furthermore, it can also be prepared by dissolving trehalose, maltose and / or maltotriose in pure water. In particular, the method of allowing glycosyltrehalose synthase and trehalose separating enzyme to act on liquefied starch together with starch debranching enzyme and cyclomaltodextrin-glucan transferase is more suitable for use because it can prepare the target trehalose-containing sugar solution through a series of enzyme reactions using starch as a raw material. In addition, when the trehalose content is less than 70% by mass, it is optionally purified by chromatography separation or the like.

[0077] <Step (B) (Step of powdering the trehalose-containing sugar solution by spray drying)>

[0078] This process is a process of supplying a sugar solution containing trehalose to spray drying to powderize it. The type of spray drying method or its conditions are not particularly limited as long as a powder containing trehalose dihydrate crystals with excellent emulsification ability can be produced. For example, a rotary atomizer method (rotating disk method), a nozzle method using a pressurized nozzle or a two-fluid nozzle, etc. can be used to spray the sugar solution containing trehalose to micronize it and increase the surface area per unit volume. For example, it can be continuously exposed to hot air at an inlet temperature of 120 to 200°C and an outlet temperature of 60 to 100°C, and powdered by instant drying. In particular, from the viewpoint of being able to obtain a powder with a narrow particle size distribution and high fluidity, a rotary atomizer method is preferred. In addition, optionally, trehalose dihydrate crystals as seeds are added to the sugar solution containing trehalose, and after a part of the trehalose dihydrate crystals are precipitated, spray drying is performed. When spray drying the sugar paste, since it contains solid components, a rotary atomizer method is preferred.

[0079] <Step (C) (Step of Crystallizing Trehalose Dihydrate Crystals)>

[0080] This step is a crystallization step of trehalose dihydrate crystals, characterized in that the trehalose-containing powder obtained in the above step (B) is aged for 7 days (24 hours × 7 days = 168 hours) or more at a relative humidity of 60% or more. When the relative humidity is less than 60%, the crystallization of trehalose dihydrate crystals cannot be promoted, and most of them remain amorphous, becoming a powder with a smooth surface, and the specific surface area becomes small, and the expected emulsification ability cannot be obtained, which is not preferred. In addition, although the aging time is controlled by the aging conditions (humidity and temperature), if it is less than 7 days, it sometimes becomes a powder with a smooth surface and a reduced specific surface area. As a result, the expected emulsification ability cannot be obtained, which is not preferred. It should be noted that the temperature during aging is not particularly limited as long as it can produce a powder containing trehalose dihydrate crystals with excellent emulsification ability. For example, the temperature can be 10 to 40°C.

[0081] <Step (D) (Step of Drying the Powder Containing Trehalose Dihydrate Crystals)>

[0082] This step is a step of drying the powder containing trehalose dihydrate crystals obtained in the above step (C) to obtain the final product. The drying method is not particularly limited as long as the desired powder can be produced. For example, a fluidized bed drying method in which the powder is floated in an air flow at a temperature of 40 to 80°C while evaporating water may be used, or a vacuum drying method in which the water content of the powder is evaporated under a reduced pressure environment may be used.

[0083] From the perspective of producing a powder having a better emulsifying ability, in the step of preparing a sugar solution containing trehalose, the method for producing a powder containing trehalose dihydrate crystals of the present invention preferably prepares a sugar solution containing 78% by mass or more and 86% by mass or less of trehalose calculated as an anhydrous substance, and containing 4% by mass or more of maltose and / or maltotriose in total calculated as an anhydrous substance.

[0084] 4. Use of the powder containing trehalose dihydrate crystals of the present invention

[0085] The powder containing trehalose dihydrate crystals of the present invention can be mixed with a hydrophobic substance and emulsified by adding water, and can therefore be advantageously used as an emulsifier for hydrophobic substances such as rapeseed oil, soybean oil, corn oil, sunflower oil, sesame oil, safflower oil, cottonseed oil, olive oil, palm oil, peanut oil, coconut oil, cocoa butter, avocado oil, margarine, shortening, etc., animal fats such as milk fat, beef tallow, lard, sheep tallow, horse tallow, whale oil, rabbit fat, chicken fat, liver oil, saturated fatty acids such as lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, unsaturated fatty acids such as oleic acid, linoleic acid, α-linolenic acid, eicosapentaenoic acid, docosahexaenoic acid, and fat-soluble vitamins such as vitamin A, vitamin D, vitamin E, and vitamin K.

[0086] As described above, the powder containing trehalose dihydrate crystals of the present invention can be used alone as an emulsifier, but can also be used in combination with other emulsifiers such as lecithin, saponin, sodium caseinate, glycerol fatty acid ester, sorbitan fatty acid ester, propylene glycol fatty acid ester, sucrose fatty acid ester, oxyethylene fatty acid alcohol, sodium oleate, morpholine fatty acid salt, polyoxyethylene higher fatty acid alcohol, calcium stearoyl lactylate, monoglyceride ammonium phosphate, alkyl polyoxyethylene ether, etc. In addition, the powder containing trehalose dihydrate crystals of the present invention can also be advantageously used in combination with a thickening stabilizer such as gum arabic, guar gum, tamarind gum, locust bean gum, carrageenan, pectin, carboxymethyl cellulose, xanthan gum, gellan gum, dextran, and pullulan as needed.

[0087] In addition, the powder containing trehalose dihydrate crystals of the present invention dissolves quickly in water and does not form lumps when dissolved, so that even when directly mixed with a material with less water content such as dough or cream, trehalose can be uniformly dispersed in food materials. Therefore, when trehalose is added to such a material, the powder containing trehalose dihydrate crystals of the present invention can omit the step of dissolving trehalose in water in advance, which is a necessary step for conventional powders containing trehalose dihydrate crystals, and can be applied to the production of food or cosmetics, quasi-drugs, and drugs with less water content.

[0088] The powder containing trehalose dihydrate crystals of the present invention can be used in the same manner as the conventional powder containing trehalose dihydrate crystals, for example, it can be used to manufacture foods such as Chinese desserts, Western desserts, snacks, ice desserts, canned foods, frozen foods, instant foods, pickles, Japanese country-style stewed food (Tsukudani), soup products, dairy products, liquid foods, weaning foods, health foods, refreshing drinks, carbonated beverages, fruit juice drinks, vegetable juices, milk drinks, coffee, black tea drinks, oolong tea drinks, green tea drinks, barley tea drinks, alcoholic beverages, cosmetics such as lotions, beauty essences, emulsions, creams, foundations, mascara, lipsticks, nail polishes, makeup removers, facial cleansers, mouthwashes, shampoos, conditioning liquids, conditioners, perming agents, perfumes, quasi-drugs, and pharmaceuticals.

[0089] The present invention will be described in more detail below based on experiments.

[0090] <Experiment 1-1: Comparison of emulsifying abilities of powders containing trehalose dihydrate crystals prepared from various sugar solutions having different trehalose contents>

[0091] In order to investigate the effect of trehalose content on the emulsifying ability of a powder containing trehalose dihydrate crystals, various sugar solutions with different trehalose contents were prepared, and powders containing trehalose dihydrate crystals were prepared by spray drying, and then the emulsifying ability was measured.

[0092] Corn starch was suspended in pure water to a solid content concentration of 33% by mass, calcium chloride was added to a concentration of 0.1% by mass, and the pH was adjusted to 6.0 to obtain a starch suspension. Heat-resistant α-amylase (trade name "Spitase HK", manufactured by Nagase ChemteX) was added to the starch suspension at a ratio of 10 units per 1g of solid content, and the mixture was passed through a continuous liquefaction device at a flow rate of 1L / min while reacting at 100°C for 25 minutes, and then heated at 140°C for 5 minutes to stop the enzyme reaction and obtain a starch liquefied liquid. The obtained starch liquefied liquid was cooled to 50°C, and an enzyme solution containing α-glycosyltrehalose synthase and trehalose separating enzyme prepared by the method described in Experiment 1-1 of International Publication No. 2013 / 042587 was added thereto in an amount of 2 units and 10 units, respectively, per 1g of starch, and then 300 units of isoamylase (manufactured by Hayashihara Co., Ltd.) per 1g of starch and 2 units of CGTase derived from Paenibacils Illinois Sensis NBRC15959 strain prepared by the method described in Experiment 1-2 of International Publication No. 2013 / 042587 were added per 1g of starch, and the mixture was reacted for 11 hours, and then 10 units of α-amylase (trade name "NeoSpitase PK-2", sold by Nagase ChemteX) was added per 1g of starch, and the reaction was carried out at 80°C for 2 hours, followed by heating at 100°C for 30 minutes to stop the enzyme reaction, thereby obtaining a saccharified liquid. The obtained saccharified liquid was decolorized using activated carbon, desalted using an ion exchange resin, and then concentrated to a solid content concentration of 30% by mass to obtain a trehalose-containing sugar liquid 1 having a sugar composition shown in Table 1.

[0093] In addition, in the trehalose production reaction step, except that α-glycosyltrehalose synthase, trehalose separating enzyme, isoamylase and CGTase were allowed to act on the starch liquefied liquid for 48 hours, the same operation was carried out as above to obtain a trehalose-containing sugar solution 5 having a solid content concentration of 30% by mass and having a sugar composition as shown in Table 1.

[0094] On the other hand, a commercially available powder containing trehalose dihydrate crystals (trade name "Treha Micro Powder", manufactured by Hayashibara Co., Ltd.) was dissolved in pure water to a solid content concentration of 30% by mass to obtain a trehalose-containing sugar solution 9 having a solid content concentration of 30% by mass and having a sugar composition as shown in Table 1.

[0095] Next, trehalose-containing sugar liquid 1 and trehalose-containing sugar liquid 5 were mixed at an appropriate ratio to prepare trehalose-containing sugar liquids 2 to 4 having sugar compositions shown in Table 1, respectively. Also, trehalose-containing sugar liquid 5 and trehalose-containing sugar liquid 9 were mixed at an appropriate ratio to prepare trehalose-containing sugar liquids 6 to 8 having sugar compositions shown in Table 1, respectively.

[0096] [Table 11

[0097]

[0098] The trehalose-containing sugar solutions 1 to 9 prepared above with a solid content concentration of 30% by mass were spray-dried using a rotary atomizer (rotating disk) spray dryer at an inlet temperature of 180°C, an outlet temperature of 90°C, and a supply rate of 2L / hour to obtain various powders 1 to 9 with different trehalose contents. Then, the powders 1 to 9 were aged at a temperature of 25°C and a high humidity of 75% or 90% relative humidity, and a portion of each powder was taken before the ripening, 1 day, 5 days, and 7 days after the start of the ripening. After vacuum drying each of the collected powders at 25°C for 18 hours, the emulsifying ability was measured by the above method. In addition, the crystallinity of the trehalose dihydrate crystals was measured for each powder that was ripened for 7 days. In this experiment, the conventional trehalose dihydrate crystal powder (trade name "Treha Micro Powder", manufactured by Hayashihara Co., Ltd.) manufactured by a conventional crystallization method (i.e., crystallization-honey separation method) was used as a control powder. The results are shown in Table 2. In addition, in the table, the emulsifying ability values ​​of 0.35 or more and 0.45 or more are indicated by "*" and "**", respectively.

[0099] [Table 2]

[0100]

[0101] RH: Relative humidity (%)

[0102] As shown in Table 2, the emulsifying ability of powder 1 having a trehalose content of 64.3% by mass and powders 7 to 9 having a trehalose content of 93.0% by mass or more was hardly increased after aging, and even after 7 days of aging, the emulsifying ability value was still maintained at 0.12 to 0.27, confirming that there was no significant difference between the control powder having an emulsifying ability value of 0.10. On the other hand, the emulsifying ability value of powders 2 to 6 having a trehalose content in the range of 73.8 to 88.1% by mass increased with aging, and after 7 days of aging, the emulsifying ability showed a significantly high value of 0.39 to 0.52. In particular, the emulsifying ability of powders 3 to 5 having a trehalose content in the range of 77.5 to 85.7% by mass after aging for 7 days showed a significantly high value of 0.45 to 0.52. It should be noted that the emulsifying ability of powders 1 to 9 did not change significantly after aging for 7 days.

[0103] Similarly, as shown in Table 2, the crystallinity of the trehalose dihydrate crystals of Powders 2 to 6 showing an emulsifying ability value of 0.35 or more was 29.5% or more, and in particular, the crystallinity of the trehalose dihydrate crystals of Powders 3 to 5 showing an emulsifying ability value of 0.45 or more was 56.1% or more. In addition, in the powder X-ray diffraction patterns of Powders 1 to 9, no peak other than the diffraction peak derived from the trehalose dihydrate crystals was detected, and it was confirmed that these powders contained substantially no crystals other than the trehalose dihydrate crystals.

[0104] From these results, it can be seen that the powder obtained by spray-drying a trehalose-containing sugar solution having a trehalose content of 70% to 90% by mass and aging for 7 days or more, and the crystallinity of the trehalose dihydrate crystals increased to 25% or more, showed excellent emulsification ability. In particular, the powder obtained by spray-drying a trehalose-containing sugar solution having a trehalose content of 78% to 86% by mass and aging for 7 days or more, and the crystallinity of the trehalose dihydrate crystals increased to 50% or more, showed even more excellent emulsification ability.

[0105] <Experiment 1-2: Effect of Sugars Other Than Trehalose on the Emulsification Ability of Powders Containing Trehalose Dihydrate Crystals>

[0106] Next, in order to investigate the influence of sugars other than trehalose on the emulsifying ability of the powder containing trehalose dihydrate crystals, trehalose-containing sugar solutions containing trehalose and glucose, maltose, maltotriose, sorbitol or maltitol as a contaminant sugar were prepared, and powder containing trehalose dihydrate crystals was prepared by spray drying, and then the emulsifying ability was measured.

[0107] As a sugar solution containing trehalose, a solution containing 85% by mass of trehalose in terms of anhydrous content, and 15% by mass of glucose (sold by Wako Pure Chemical Industries, Ltd.), maltose (trade name "MALTOSE999", sold by Hayashibara Co., Ltd.), maltotriose (trade name "MALTOTRIOSE", sold by Hayashibara Co., Ltd.), sorbitol (sold by Wako Pure Chemical Industries, Ltd.), and maltitol (sold by Wako Pure Chemical Industries, Ltd.) in terms of anhydrous content was prepared to have a solid content concentration of 30% by mass, and the obtained solution was spray-dried in the same manner as in Experiment 1-1. Then, the obtained powder was aged at a temperature of 25°C and a relative humidity of 75% for 7 days, and then vacuum-dried at 25°C for 18 hours to obtain powders A to E containing glucose, maltose, maltotriose, sorbitol, or maltitol as contaminated sugars, respectively. Then, the emulsifying ability of powders A to E and the crystallinity of trehalose dihydrate crystals were measured by the above method. In this experiment, as control powders, powders F to H were prepared by simply mixing 85% by mass of trehalose dihydrate crystal powder (reagent, trade name "Trehalose 999", sold by Hayashibara Co., Ltd.) based on an anhydrous conversion, 15% by mass of β-maltose monohydrate crystal powder (reagent, trade name "MALTOSE 999", sold by Hayashibara Co., Ltd.) based on an anhydrous conversion, maltose amorphous powder (prepared by the same method as the above "standard sample of trehalose-containing powder substantially composed of amorphous substances" except that the above β-maltose monohydrate crystal powder was used as a raw material), or maltotriose amorphous powder (trade name "MALTOTRIOSE", sold by Hayashibara Co., Ltd.) and the emulsifying ability was similarly examined. The results are shown in Table 3.

[0108] [Table 31

[0109]

[0110] *: Crystallinity of mixed powder containing trehalose dihydrate crystals

[0111] As shown in Table 3, the crystallinity of powders A and B obtained by spray-drying and ripening a trehalose-containing sugar solution containing glucose or maltose as an intervening sugar substance showed a crystallinity of 86.1 to 86.6%, which was equivalent to each other, but powder A showed almost no emulsification ability, while powder B showed a significantly high value of 0.46 in terms of emulsification ability. On the other hand, the crystallinity of powders C to E obtained by spray-drying and ripening a trehalose-containing sugar solution containing maltotriose, sorbitol or maltitol as an intervening sugar substance was 70.6 to 74.4%, which was equivalent to each other, but powders D and E showed almost no emulsification ability, while powder C showed a significantly high value of 0.47 in terms of emulsification ability. In addition, in the powder X-ray diffraction patterns of each powder A to E, no peak other than the diffraction peak derived from trehalose dihydrate crystals was detected, and it was confirmed that these powders did not contain almost any crystals other than trehalose dihydrate crystals.

[0112] Similarly, as shown in Table 3, powders F to H prepared by simply mixing trehalose dihydrate crystal powder with β-maltose monohydrate crystal powder, maltose amorphous powder or maltotriose amorphous powder showed almost no emulsifying ability. In contrast, powders B and C obtained by spray-drying and ripening a trehalose-containing sugar solution containing maltose or maltotriose as an intervening sugar substance showed emulsifying abilities of 0.46 and 0.47, respectively, both of which were significantly high values. In view of the principle of spray drying in which a raw sugar solution is atomized by spraying and powdered by instant drying, it is believed that each powdered particle reflects the sugar composition of the raw sugar solution, and therefore it is believed that the powder obtained by spray drying is composed of particles containing trehalose, maltose and / or maltotriose. Furthermore, since part of the trehalose contained in the powder is converted from an amorphous state to a dihydrate crystal form by aging, it is considered that in each powder particle, trehalose in the form of dihydrate crystals and amorphous trehalose are mixed. That is, in each powder particle, the powder obtained by spray-drying and aging a sugar solution containing trehalose contains trehalose in the form of dihydrate crystals and amorphous trehalose at a predetermined ratio, and also contains amorphous maltose and / or maltotriose mixed together. From this point of view, it is different from a powder prepared by simply mixing maltose powder and / or maltotriose powder with a conventionally known trehalose dihydrate crystal powder, and it is considered important in terms of exerting emulsification ability as a form of such a powder.

[0113] From these results, it is understood that, for a powder containing trehalose dihydrate crystals, even if the trehalose content and the crystallinity of the trehalose dihydrate crystals are the same, the emulsifying ability of the powder differs depending on the type of the concomitant saccharide and the form in which it exists, and further, it is impossible to produce a powder containing trehalose dihydrate crystals having excellent emulsifying ability by simple mixing, but a trehalose-containing sugar solution containing maltose and / or maltotriose as concomitant saccharides is spray-dried and ripened to produce a powder containing trehalose dihydrate crystals composed of particles containing trehalose, maltose and / or maltotriose at a predetermined ratio, thereby, for the first time, a powder containing trehalose dihydrate crystals having excellent emulsifying ability can be obtained.

[0114] It is to be noted that, although specific data are omitted, for the five powder particles in the powder B, one particle of each powder particle (about 0.3 mg / particle) was collected with tweezers, dissolved in 25 μL of pure water, and subjected to the above HPLC analysis to investigate the sugar composition. As a result, all the powder particles had substantially the same sugar composition, that is, trehalose content of 85±1% by mass and maltose content of 15±1% by mass. On the other hand, the same operation was performed on the powder F prepared by simply mixing the powder containing trehalose dihydrate crystals and the powder containing maltose monohydrate crystals, and the sugar composition of each of the five particles was investigated. As a result, either a particle containing 99.9% by mass of trehalose or a particle containing 99.9% by mass of maltose was detected. As can be seen from this, when investigating the sugar composition of one powder particle, there is a clear difference between the powder containing trehalose dihydrate crystals of the present invention and a simple mixture of a commercially available powder containing trehalose dihydrate crystals and a powder containing maltose.

[0115] From the results of Experiment 1-2, it is known that in order to produce a powder containing trehalose dihydrate crystals having emulsifying ability, it is important to spray-dry and ripen a trehalose-containing sugar solution containing maltose and / or maltotriose as an impure sugar. Therefore, for the powder containing trehalose dihydrate crystals having excellent emulsifying ability prepared in Experiments 1-1 and 1-2, powders 2 to 6, and powders B and C, the results are summarized in Table 4, focusing on the total maltose content and maltotriose content.

[0116] [Table 4]

[0117]

[0118] RH: Relative humidity (%)

[0119] As shown in Table 4, the total maltose content and maltotriose content of powders 2 to 6, powder B, and powder C, which have emulsifying power values ​​of 0.35 or more, are 3.7% by mass or more, the trehalose content is in the range of 73.8% by mass or more and 88.1% by mass or less, and the crystallinity is in the range of 29.5% or more and 86.1% or less. In particular, the total maltose content and maltotriose content of powders 3 to 5, which have emulsifying power values ​​of 0.45 or more, are 4.4% by mass or more, the trehalose content is in the range of 77.5% by mass or more and 85.7% by mass or less, and the crystallinity is in the range of 56.1% or more and 86.1% or less. On the other hand, although not shown in Table 4, as shown in Table 2, powders 7 to 9, which have low emulsifying power values ​​of 0.26 or less, have a high trehalose content of 93.0% or more, a total maltose content and maltotriose content of less than 3% by mass, and a crystallinity of 74.5% to 89.3%. Even though the crystallinity was the same, the emulsifying ability of powders 7 to 9 was low, presumably because the maltose content and maltotriose content were low.

[0120] Based on the findings obtained from Experiments 1-1 and 1-2, it was found that a powder containing 70% to 90% by mass of trehalose in an anhydrous form and a total of 3% by mass or more of maltose and / or maltotriose in an anhydrous form, and a trehalose dihydrate crystal-containing powder having a crystallinity of 25% to less than 90% had an emulsifying power of 0.35 or more. In particular, a powder containing 78% to 86% by mass of trehalose in an anhydrous form and a total of 4% by mass or more of maltose and / or maltotriose in an anhydrous form, and a trehalose dihydrate crystal-containing powder having a crystallinity of 50% to less than 90% had an emulsifying power of 0.45 or more.

[0121] <Experiment 2: Observation of the Powder Surface of the Powder Containing Trehalose Dihydrate Crystals Using a Scanning Electron Microscope>

[0122] In order to clarify the difference in structure between the powder containing trehalose dihydrate crystals having excellent emulsification ability and the powder containing trehalose dihydrate crystals having substantially no emulsification ability, the powder surface was observed using a scanning electron microscope.

[0123] The surfaces of powders 1, 3, 4, 5 and 9 obtained in Experiment 1-1 (aged for 7 days at a relative humidity of 75%) were observed using a scanning electron microscope ("SU3500", manufactured by Hitachi High Technologies). Figures 1 to 5 shown.

[0124] like Figure 1 and 5As shown, the surfaces of powders 1 and 9 are relatively smooth. Figures 2 to 4 As shown, a large number of fine irregularities were observed on the surface of powders 3 to 5. The crystallinity of the trehalose dihydrate crystals of powder 1 was as low as 4.6%, and most of it remained in an amorphous state, so it was estimated that it was a powder with a smooth surface. In addition, the crystallinity of the trehalose dihydrate crystals of powder 9 was as high as 84.6%, and most of it was crystals, so it was estimated that it was a powder with a smooth surface. On the other hand, the crystallinity of the trehalose dihydrate crystals of powders 3 to 5 was 55.7 to 59.5%, and it contained amorphous and crystals in moderation, so it was estimated that it was a powder with many irregularities on the surface. These results suggest that powders containing trehalose dihydrate crystals with many fine irregularities on the surface have excellent emulsification ability.

[0125] <Experiment 3: Measurement of specific surface area of ​​powder containing trehalose dihydrate crystals>

[0126] In Experiment 2, a large number of fine irregularities were observed on the surface of the powder containing trehalose dihydrate crystals having excellent emulsification ability compared to the powder containing trehalose dihydrate crystals having substantially no emulsification ability, and thus the specific surface area of ​​the powder containing trehalose dihydrate crystals having excellent emulsification ability was measured.

[0127] The specific surface area of ​​powders 2 to 6 obtained in Experiment 1-1 (aged for 7 days at a relative humidity of 75%) was measured by the above method. As a control powder, conventional trehalose dihydrate crystal powder (trade name "Treha Micro Powder", manufactured by Hayashihara Co., Ltd.) was used. The results are shown in Table 5.

[0128] [Table 5]

[0129]

[0130] As shown in Table 5, the specific surface area of ​​the control powder, which showed almost no emulsification ability, was 0.18 m 2 / g, compared with this, the specific surface areas of the powders 2 to 6 having an emulsification capacity of 0.35 or more were 0.26 to 0.61 m 2 In particular, the specific surface areas of the powders 3 to 5 having an emulsification capacity of 0.45 or more are 0.36 to 0.61 m 2 Although it is not possible to determine whether there is a close correlation between the value of emulsifying ability and the specific surface area, these results indicate that the powder containing trehalose dihydrate crystals with an emulsifying ability value of 0.35 or more has an emulsifying ability value of 0.25 m 2 The specific surface area of ​​the powder containing trehalose dihydrate crystals is greater than 0.35 m / g, and the emulsification capacity value is greater than 0.45. 2 / g or more specific surface area.

[0131] The present invention will be described in more detail below with reference to the following examples, but the technical scope of the present invention is not to be construed in any limiting manner by these examples.

[0132] Example 1

[0133] <Powder containing trehalose dihydrate crystals>

[0134] A trehalose solution having a solid content concentration of 30% and containing 85.7% by mass of trehalose, 2.9% by mass of maltose and 1.5% by mass of maltotriose calculated as anhydrous was prepared in the same manner as in Experiment 1-1. The obtained trehalose solution was spray dried using a spray dryer ("L-8 type spray dryer", manufactured by Okawara Chemical Industry Co., Ltd.). It should be noted that the spray drying was carried out using a sprayer method under the conditions of an inlet temperature of 180°C, an outlet temperature of 90°C, and a supply rate of 2L / hour. The obtained powder was aged at a temperature of 25°C and a relative humidity of 60% for 7 days, and then vacuum dried at 25°C for 18 hours to produce a powder containing trehalose dihydrate crystals.

[0135] The emulsifying ability, crystallinity and specific surface area of ​​trehalose dihydrate crystals of this product were measured and the results were 0.51, 46.9% and 0.61m 2 / g. In addition, the particle size distribution and structure of this product were measured, and the particles with a particle size of 53μm or more and less than 300μm accounted for 60% by mass of the whole powder, and the particles with a particle size of less than 53μm accounted for 20% by mass of the whole powder. It should be noted that after taking one powder particle (about 0.3mg) from this product with tweezers, it was dissolved in 25μL of pure water, and the sugar composition was analyzed by HPLC according to the conventional method. The results showed that it had basically the same sugar composition as the above-mentioned trehalose solution as the spray drying raw material. This product has excellent emulsifying ability and is therefore particularly suitable for the manufacture of foods and cosmetics containing a large amount of oils and fats. In addition, like the previous powder containing trehalose dihydrate crystals, it can be optionally used as a food material and a cosmetic material.

[0136] Example 2

[0137] <Powder containing trehalose dihydrate crystals>

[0138] A trehalose solution having a solid content concentration of 30% and containing 80.9% by mass of trehalose, 3.0% by mass of maltose and 2.3% by mass of maltotriose calculated as anhydrous was prepared in the same manner as in Experiment 1-1. The obtained trehalose-containing sugar solution was spray-dried using a spray dryer ("L-8 type spray dryer", manufactured by Ohkawara Chemical Industry Co., Ltd.). It should be noted that the spray drying was carried out using a sprayer method under the conditions of an inlet temperature of 180°C, an outlet temperature of 90°C, and a supply rate of 2L / hour. The obtained powder was aged at a temperature of 20°C and a relative humidity of 60% for 7 days, and then vacuum dried at 25°C for 18 hours to produce a powder containing trehalose dihydrate crystals.

[0139] The emulsification ability, crystallinity and specific surface area of ​​this product were measured to be 0.46, 43.2% and 0.49 m 2 / g. In addition, the particle size distribution of this product was measured, and the result showed that the particles with a particle size of 53 μm or more and less than 300 μm accounted for 62% by mass of the whole powder, and the particles with a particle size of less than 53 μm accounted for 18% by mass of the whole powder. This product has excellent emulsifying ability and is therefore particularly suitable for the manufacture of foods and cosmetics containing a large amount of fats. In addition, similar to the conventional powder containing trehalose dihydrate crystals, it can be optionally used as a food material and a cosmetic material.

[0140] Example 3

[0141] <Powder containing trehalose dihydrate crystals>

[0142] A trehalose solution having a solid content concentration of 30% and containing 73.7% by mass of trehalose, 3.5% by mass of maltose and 3.4% by mass of maltotriose calculated as anhydrous was prepared in the same manner as in Experiment 1-1. The obtained trehalose-containing sugar solution was spray-dried using a spray dryer ("L-8 type spray dryer", manufactured by Ohkawara Chemical Industry Co., Ltd.). It should be noted that the spray drying was carried out using a sprayer method under the conditions of an inlet temperature of 180°C, an outlet temperature of 90°C, and a supply rate of 2L / hour. The obtained powder was aged at a temperature of 20°C and a relative humidity of 60% for 7 days, and then vacuum dried at 25°C for 18 hours to produce a powder containing trehalose dihydrate crystals.

[0143] When the emulsification ability, crystallinity and specific surface area of ​​this product were measured, they were 0.43, 32.8% and 0.30m 2 / g. In addition, the particle size distribution of this product was measured, and the result showed that the particles with a particle size of 53 μm or more and less than 300 μm accounted for 65% by mass of the whole powder, and the particles with a particle size of less than 53 μm accounted for 12% by mass of the whole powder. This product has excellent emulsifying ability and is therefore particularly suitable for the manufacture of foods and cosmetics containing a large amount of fats. In addition, similar to the conventional powder containing trehalose dihydrate crystals, it can be optionally used as a food material and a cosmetic material.

[0144] Example 4

[0145] <Powder containing trehalose dihydrate crystals>

[0146] A trehalose solution containing 85.2% by mass of trehalose, 3.0% by mass of maltose and 1.8% by mass of maltotriose in terms of anhydrous conversion was prepared by the same method as in Experiment 1-1, and then concentrated to a solid content concentration of 70%. To the obtained trehalose-containing sugar solution, 2% by mass of trehalose dihydrate crystals in terms of anhydrous conversion were added as seeds, and the mixture was left to stand at room temperature for 12 hours to prepare a sugar paste, which was then spray-dried using a spray dryer ("L-8 type spray dryer", manufactured by Ohkawara Chemical Industry Co., Ltd.). It should be noted that the spray drying was performed using a sprayer method under the conditions of an inlet temperature of 180°C, an outlet temperature of 90°C, and a supply rate of 2L / hour. The obtained powder was aged at a temperature of 25°C and a relative humidity of 60% for 7 days, and then vacuum-dried at 25°C for 18 hours to produce a powder containing trehalose dihydrate crystals.

[0147] The emulsification ability, crystallinity and specific surface area of ​​the product were measured and the results were 0.48, 69.6% and 0.50m 2 / g. In addition, the particle size distribution of this product was measured, and the result showed that the particles with a particle size of 53 μm or more and less than 300 μm accounted for 68% by mass of the whole powder, and the particles with a particle size less than 53 μm accounted for 15% by mass of the whole powder. This product has excellent emulsifying ability and is therefore particularly suitable for foods and cosmetics containing a large amount of oil. In addition, similar to the conventional powder containing trehalose dihydrate crystals, it can be optionally used as a food material and a cosmetic material.

[0148] Example 5

[0149] <Powdered Soup>

[0150] 35 parts by mass of α-corn starch powder, 12 parts by mass of α-waxy corn starch, 4 parts by mass of α-potato starch powder, 10 parts by mass of the powder containing trehalose dihydrate crystals obtained in Example 1, 7 parts by mass of skimmed milk powder, 7 parts by mass of sodium chloride, and 0.5 parts by mass of onion powder were mixed, and 10 parts by mass of vegetable hydrogenated oil melted by heating was added thereto. The obtained mixture was granulated using a fluidized bed granulator and then dried under hot air at 70° C. to produce a powdered soup.

[0151] When this product is dissolved in hot water, the oily components are evenly dispersed, so that it becomes a powdered corn soup with a smooth texture and good flavor.

[0152] Example 6

[0153] <Bath Additive>

[0154] 15 parts by weight of the powder containing trehalose dihydrate crystals obtained in Example 1 and 5 parts by weight of fumaric acid were added to a Nauta mixer (rotation speed 100 rpm, jacket temperature 55° C.), and then 3 parts by weight of isopropyl palmitate and 1 part by weight of octyldodecyl myristate were slowly added, and then an appropriate amount of fragrance was added and mixed. Then, the obtained mixture was granulated using an extrusion granulator to produce a bath agent.

[0155] When this product is dissolved in hot water, the oily components are evenly dispersed, so it is a bath agent that is lubricated in hot water and has an excellent feel when used.

[0156] Comparative Example 1

[0157] <Powder containing trehalose dihydrate crystals>

[0158] A powder containing trehalose dihydrate crystals was produced in the same manner as in Example 4 except that the aging period was changed to 5 days. The emulsifying ability of the product and the crystallinity of the trehalose dihydrate crystals were measured and found to be 0.28 and 68.8%, respectively, indicating that the product did not have an excellent emulsifying ability.

[0159] From the comparison between Example 4 and Comparative Example 1, it can be seen that even when seed crystals were added to a sugar solution containing trehalose and the obtained sugar mass was spray-dried, a powder having excellent emulsifying ability could not be obtained when the aging period of the obtained powder was 5 days. In contrast, a powder having excellent emulsifying ability was obtained when the aging period of the powder obtained by spray drying was 7 days or more. These results show that in order to produce a powder containing trehalose dihydrate crystals having excellent emulsifying ability, it is important to age the powder obtained by spray-drying a sugar solution containing trehalose at a relative humidity of 60% or more for 7 days or more, regardless of whether seed crystals are added.

[0160] Industrial Applicability

[0161] As can be seen from the above description, the powder containing trehalose dihydrate crystals of the present invention has excellent emulsification ability and can be expected to be effectively used in various fields including food and cosmetics. The present invention is a very significant invention that has made a great contribution to the field.

Claims

1. A powder containing α,α-trehalose dihydrate crystals, comprising particles containing α,α-trehalose, maltose and / or maltotriose, having the following characteristics (1) to (4): (1) containing 70% by mass or more and 90% by mass or less of α,α-trehalose calculated as anhydrous; (2) containing 3% by weight or more of maltose and / or maltotriose in total, calculated as anhydrous; (3) the crystallinity of the α,α-trehalose dihydrate crystals calculated based on the powder X-ray diffraction pattern is 25% or more and less than 90%, and (4) No diffraction peaks derived from maltose and maltotriose crystals were detected in the powder X-ray diffraction pattern.

2. The powder containing α,α-trehalose dihydrate crystals according to claim 1, further having the following feature (5): (5) The specific surface area of ​​the powder measured by nitrogen adsorption method was 0.25 m 2 / g or above.

3. The powder containing α,α-trehalose dihydrate crystals according to claim 1 or 2, further having the following feature (6): (6) Contains Particles with a particle size of 53 μm or more and less than 300 μm account for at least 50% by mass of the entire powder, and Particles with a particle size of less than 53 μm account for 10% by mass or more of the entire powder.

4. The powder containing α,α-trehalose dihydrate crystals according to claim 1 or 2, further having the following feature (7): (7) 5 parts by mass of the powder and 1 part by mass of corn oil were mixed, and then 500 parts by mass of pure water were added and stirred to obtain an emulsion having a turbidity of 0.35 or more at a wavelength of 720 nm.

5. The method for producing a powder containing α,α-trehalose dihydrate crystals according to any one of claims 1 to 4, characterized in that: Including the following processes: A step of preparing a sugar solution containing 70% by mass or more and 90% by mass or less of α,α-trehalose calculated as an anhydrous substance and 3% by mass or more of maltose and / or maltotriose calculated as an anhydrous substance, The step of powdering the sugar solution by spray drying, The obtained powder is aged at a relative humidity of 60% or more for 7 days or more to form α,α-trehalose dihydrate crystals, and A step of drying the obtained powder containing α,α-trehalose dihydrate crystals.

6. The method for producing a powder containing α,α-trehalose dihydrate crystals according to claim 5, characterized in that: The step of preparing a sugar solution containing 70% by mass or more and 90% by mass or less of α,α-trehalose calculated as anhydrous and 3% by mass or more of maltose and / or maltotriose calculated as anhydrous is carried out by allowing glycosyltrehalose synthase and trehalose separating enzyme to act on liquefied starch together with debranching enzyme and cyclomaltodextrin-glucan transferase.

7. The method for producing a powder containing α,α-trehalose dihydrate crystals according to claim 5 or 6, characterized in that: Spray drying is carried out by means of a rotary atomizer.

8. An emulsifier, characterized in that A powder comprising the α,α-trehalose dihydrate crystals according to any one of claims 1 to 4.

9. The powder containing α,α-trehalose dihydrate crystals according to claim 3, further having the following feature (7): (7) 5 parts by mass of the powder and 1 part by mass of corn oil were mixed, and then 500 parts by mass of pure water were added and stirred to obtain an emulsion having a turbidity of 0.35 or more at a wavelength of 720 nm.

10. The method for producing a powder containing α,α-trehalose dihydrate crystals according to claim 9, characterized in that: Including the following processes: A step of preparing a sugar solution containing 70% by mass or more and 90% by mass or less of α,α-trehalose calculated as an anhydrous substance and 3% by mass or more of maltose and / or maltotriose calculated as an anhydrous substance, The step of powdering the sugar solution by spray drying, The obtained powder is aged at a relative humidity of 60% or more for 7 days or more to form α,α-trehalose dihydrate crystals, and A step of drying the obtained powder containing α,α-trehalose dihydrate crystals.

11. The method for producing a powder containing α,α-trehalose dihydrate crystals according to claim 10, characterized in that: The step of preparing a sugar solution containing 70% by mass or more and 90% by mass or less of α,α-trehalose calculated as anhydrous and 3% by mass or more of maltose and / or maltotriose calculated as anhydrous is carried out by allowing glycosyltrehalose synthase and trehalose separating enzyme to act on liquefied starch together with debranching enzyme and cyclomaltodextrin-glucan transferase.

12. The method for producing a powder containing α,α-trehalose dihydrate crystals according to claim 10 or 11, characterized in that: Spray drying is carried out by means of a rotary atomizer.